HELIUM ISOTOPES IN THE BAIKAL RIFT UNDERGROUND FLUIDS AND ITS FRAMING (TO THE GEODYNAMICS OF CONTINENTAL RIFT GENESIS) - Polyak B.G. (My University, 2000)
The aim of this paper was to generalize the results of studying the helium isotope composition in the subsurface fluids of the Baikal-Mongolia region for the last quarter of the XX century. The 3He/4He= R ratios were determined using 139 samples of the fluid-gas phase, collected at 104 sites of the Baikal Rift Zone (BRZ) and the adjacent structural features. The R values ranged from 1 10-8, characteristic of crustal radiogenic helium, to 1.1 10-5, close to the values characteristic of MORB reservoirs. The repeated collections of samples in some sites during more than 20 years proved the stable isotope composition of helium at all sites for all R values. No systematic R differences were found also in the samples collected from the outcropping rocks and from the rocks crossed by boreholes drilled in the same areas. No universal relationship was also found between the helium isotope composition and the general composition of the gas phase, yet, the lowest R values were found for the methane gas of the hydrocarbon deposits, whereas the helium composition in the nitric and carbon dioxide gases was much more variable, the maximum R values being characteristic of the latter. The fN2/fNe ratios of the carbon dioxide gases proved the excess volumes of nonatmospheric nitrogen, yet the CO2/3He ratio is different from that of MORB. The comparison of the isotopic composition of helium with its concentration and composition of the main components of the gas phase of the fluids shows that its was formed under the influence of the fractionation of the differently soluble components in the gas-water system and of the generation/consumption of the chemically active gases in the crust. The structural-tectonic elements of the region vary in the spectrum of the R values. In the pre-Riphean Siberian Platform the average value of R =(3.6 0.9) 10-8 almost coincides with the canonic radiogenic one. The Paleozoic crust of the Hangai region showed R =(16.3 4.6) 10-8, the most probable estimate being (12.3 2.9) 10-8. The structural features of the eastern flank of the Baikal Rift zone (Khentei and Dauria), involved into the Mz-Kz reactivation, showed the R values varying from 4.4 10-8 to 2.14 10-6, the average value being 0.94 10-6. The distribution of the R values across the Baikal Rift zone suggests that the heat and mass flow from the mantle was not only in the rift zone, but also in the much more eastern regions. The Baikal Rift Zone fluids show the R values varying from 4.9 10-8 to 1.1 10-5. Their variation along the rift zone strike shows a distinct regular pattern expressed in the diminishing of the R values in both directions from the Tunkin Basin. Being accompanied by the decreasing density of the conductive heat flow and by the decreasing sizes of the rift valleys, this trend proves the declining activity of the heat flow from the mantle toward the peripheral segments of the rift zone. The comparison of this trend with the data available for other continental rift zones and mid-oceanic ridges proves the principal differences between the crust and mantle interaction mechanisms in these environments. values in both directions from the Tunkin Basin. Being accompanied by the decreasing density of the conductive heat flow and by the decreasing sizes of the rift valleys, this trend proves the declining activity of the heat flow from the mantle toward the peripheral segments of the rift zone. The comparison of this trend with the data available for other continental rift zones and mid-oceanic ridges proves the principal differences between the crust and mantle interaction mechanisms in these environments.
Keywords: HELIUM ISOTOPES; BAIKAL RIFT; UNDERGROUND FLUIDS; CONTINENTAL RIFT GENESIS; MORB